MAQÄSÌ£ID ASY-SYARÄª`AH DALAM BINGKAI PEMIKIRAN ASY-SYÄTÌ£IBÄª - Nurjanah, Siti (ISTINBATH JURNAL HUKUM, 2010)
AbstractAsy-SyÄthibÄ« had used utilitarianistic methodology when he explore about maqÄsÌ£id asy-syarÄ«`ah by using texs or nash. Asy-SyÄthibÄ« has said that all of syaraâ law which is covered by text or nash has mashlahah for human. If law didnât cover mashlahah so that is stopped because it was giving for human always followed by mashlahah for doing it. Asy-SyÄthibÄ« has moderate strategyÂ  in law. MaqÄshid asy-syarÄ«`ah concept for asy-SyÄthibÄ« is looking at mashlahah for human really when five of life unsure have been taken care, there are: religion protection (hifz ad-dÄ«n), spirit protection (hifz an-nafs), intelligential protection (hifz al-`aql), eternal human protection (hifz an-nasl), and wealth protection (hifz al-mÄl). For really that reason, asy-SyÄthibÄ« divided maqÄshid asy-syarÄ«`ah for three kind, there are dharÅ«riyyÄt, hajjiyÄt, and tahsÄ«niyyÄt. All three canât be split and then, hajjiyÄt is become completer for dharÅ«riyyÄt, and tahsÄ«niyyÄt is become completer for hajjiyÄt, while dharÅ«riyyÄt is become main of hajjiyÄt and tahsÄ«niyyÄt.Keywords: utilitarianistic methodology, dharÅ«riyyÄt,Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  hajjiyÄt, tahsÄ«niyyÄt.